Library Vandalism: Causes And Prevention - Bhat, Suneel Kumar (MIER Journal of Educational Studies Trends and Practices, 2021)
Vandalism is a menace that affects all types of libraries, especially academic libraries. Academic libraries are an integral part of an institution of higher learning. Librarians are considered curators of a library collection and they need to be aware of the ills of vandalism. They should adequately be prepared to deal with this menace. This paper examines the problems of vandalism being faced by the librarians. Various types of vandalism that occur in the libraries have been reported in this paper. The researcher has also highlighted the costs associated with vandalism along with vandalism prevention strategies.